O USO DE MODELAGENS REPRESENTATIVAS COMO ESTRATÉGIA DIDÁTICA NO ENSINO DA BIOLOGIA MOLECULAR: ENTENDENDO A TRANSCRIÇÃO DO DNA - Chagas Madureira, Hérika; Aparecida de Nadrade Mortinho, Maria; Eduardo Justino de Oliveira, Carlos; Correa de Azevedo, Laís; Freitas do Carmo, Leandro (LINKSCIENCEPLACE, 2016)
Nucleic acids are the basis of heredity. Although DNA is constantly presented as an icon of science, most world’s population do not understand this scientific content, and perhaps the difficulty was due to the abstract nature of this concept. Based on these observations, it is necessary, the procedures and practices in biology, the use of didactic models, joining the playful aspects to the cognitive, in order to clarify more simply this process. Thus, the objective this work is to assist in the learning of concepts related to molecular biology, establishing a representative methodology of the structures of DNA and RNA molecules, and the transcription process. This process is the first step of the flow of genetic information. The approach outlined here is the development of a didactic, three-dimensional model of the transcription process. For this, we used materials within easy reach as the EVA rubber, wooden sticks and modeling clay. The biological models with three-dimensional and colorful structures can be used as learning facilitators, complementing the written content and the plane figures of textbooks. In addition to the visual side, the use of representative modeling enables the student to handle the material, looking from different angles, thus improving their understanding of the analyzed content.